IMPLEMENTATION OF PROGRESSIVE INNOVATION TECHOLOGIES IN ENGLISH TEACHING - Nargiza Narziyeva Ravilevna (Web of Journals Publishing, 2024)
The article refers to the methods of using modern methods of pedagogical resources in teaching English for students. It focuses on aspects such as home reading and listening.
Keywords: fantasy, issues, interactive, linguistic part, psychological part, methodical part.